Pengaruh pemahaman atas strategi bisnis, kemampuan manajerial, dan pengetahuan manajemen terhadap kinerja perusahaan coffee shop - Suwatri, Meriska; Rahman, Hafiz; Rahman, Annisa (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to determine the effect of understanding business strategy, managerial ability, and management knowledge on company performance at a coffee shop in Padang City. The research method used is quantitative research. The quantitative research approach used is associative research. The purpose of associative research in this study was to determine the effect of business strategy, managerial ability, and management knowledge on company performance at a coffee shop in Padang City. The results of this study indicate that there is a significant positive effect between understanding of business strategy, managerial ability, and knowledge management on company performance. With a business strategy, companies can improve the performance of a company and optimize performance by increasing managerial capabilities because it is important for business growth and success and improvements in knowledge management will improve performance in a company.